A Dangerous Text: Disciplining Deficient Readers and the Policing of the Qur'an in the German Islam Conference. (1st October 2020) - Aguilar, Luis Manuel Hernández; Ahmad, Zubair
Abstract : Departing from the premise that the Qur'an has been imagined as a dangerous, almost subject-like text in the long tradition of the Eurocentric-Orientalist order, this contribution traces how Germany's Islam Conference has attempted to govern this supposedly dangerous text by disciplining its readers and policing its interpretations particularly regarding gender justice and equality. In doing so we argue that the policing of the Qur'an is an important site of political interventions and as a technology of power whereby Muslims in contemporary Germany are problematised as deficient and archaic readers. Moreover, policing the Qur'an as a racialised textual governmentality, we argue, is a further point of power application within the larger context of refashioning the racialised figure of the Muslim subject in Germany.